2006
DOI: 10.1111/j.1600-0765.2006.00880.x
|View full text |Cite
|
Sign up to set email alerts
|

The epithelial cell rests of Malassez – a role in periodontal regeneration?

Abstract: This article reviews general aspects about the epithelial cell rests of Malassez (ERM). The historical and general morphological features of the ERM are briefly described. The embryological derivation of the ERM is presented as an important consideration in understanding the events associated with their origin and possible functional roles within the periodontal ligament. The ultrastructural description of the ERM is also included to complement the morphological characteristics which distinguish these cells as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
98
0
8

Year Published

2008
2008
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(107 citation statements)
references
References 82 publications
(91 reference statements)
1
98
0
8
Order By: Relevance
“…throughout life (Spouge, 1980;Bosshardt and Selvig, 1997;Rincon et al, 2006). However, it has been shown that the number of RM decreases with aging (Wentz et al, 1950;Reeve and Wentz, 1962;Simpson, 1965;Lambrichts et al, 1993;Wesselink and Beertsen, 1993;Gonçalves et al, 2008); this result was confirmed by this study, which revealed a reduction of 88.5% in the numerical density of RM profiles from 29-to 120-day-old.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…throughout life (Spouge, 1980;Bosshardt and Selvig, 1997;Rincon et al, 2006). However, it has been shown that the number of RM decreases with aging (Wentz et al, 1950;Reeve and Wentz, 1962;Simpson, 1965;Lambrichts et al, 1993;Wesselink and Beertsen, 1993;Gonçalves et al, 2008); this result was confirmed by this study, which revealed a reduction of 88.5% in the numerical density of RM profiles from 29-to 120-day-old.…”
Section: Discussionsupporting
confidence: 81%
“…In contrast, large RM have been demonstrated in determined circumstances, such as orthodontic tooth movement (Brice et al, 1991;Talic et al, 2003), inflammatory and wound healing processes of the periodontium (Johansen, 1970;Hamamoto et al, 1998;Hasegawa et al, 2003). In these abnormal conditions, the cells of RM may proliferate (Götz et al, 2003;Talic et al, 2003), resulting in the formation of odontogenic cysts and tumors (Ten Cate 1972;Spouge, 1980;Hamamoto et al, 1989Hamamoto et al, , 1998Rincon et al, 2006). Our morphometric results revealed that the number of epithelial cell profiles/RM increased according to the RM profile area; this is confirmed by the fact that either the numerical density or the area of the epithelial cells was similar in the groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…45 Recent research has demonstrated the role of the ERM in contributing to periodontal regeneration and the turnover of ERM cells throughout life. 46 The ERM exhibit a unique ability called the EMT. These cells are epithelial cells but live in the connective tissue environment with the ability to differentiate into mesenchyme-related tissues by losing their basal lamina.…”
Section: Epithelial Cell Rests Of Malassez (Erm)mentioning
confidence: 99%